Facilitating interaction with police during routine traffic stops for persons with ASD - Grindle, H.; Sassu, K.A.; Dooley, J.M.; Farmer, E.B.; Volkmar, F.R. (Journal of Autism and Developmental Disorders, 2024)
A product of ASD socio-communicative-deficits and insufficient police training related to autism, ASD-police interactions have the potential to become problematic, with negative outcomes for ASD individuals and police alike. Thus, the combination of police acclimation, simulatory experience for drivers with ASD and the introduction of Connecticut’s recent Blue Envelope could improve overall experiences for drivers. A simulated routine traffic stop practice event, utilising pre- and post- measures was conducted in an effort to quantify drivers’ feelings about current and future interactions with police. Our prediction that participants would experience a statistically significant improvement in anxiety, comfort and self-perceived knowledge levels about future ASD-police interactions immediately following the intervention was confirmed. Our prediction that initially significant disparities between participants with and without police experience – those with previous police encounters versus those that don’t - would become not significant immediately following the intervention was disconfirmed. While the longitudinal data suggested that improved post-intervention ASD psychological measures remained statistically significant in the long-term, the sample responses to our long-term questionnaire were too few in number to make any definitive conclusions. It is suggested that practice traffic stops such as these could benefit both drivers with ASD and law enforcement nationwide. It is further suggested that police officer curriculums should include additional training regarding special populations. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2024.
Keywords: ASD; ASD-police Interaction; Blue Envelope Program; Driving; Pullover; Simulation; dept.edu; dept.sed; peer-reviewed

The effects of placement method on multilingual learner success in higher education - Key Jr, William (TESOL Journal, 2024)
In the United States, many actors are pushing for the use of grade point average (GPA) as the main placement tool for gatekeeper math and English courses for community college students (Quarles, 2022; Scott-Clayton, 2018; Turk, 2017). One community college system (pseudonymously, SXCC) in a New England state has begun placing students in initial math and English classes based on self-reported GPA. There have been studies on the effects of placement changes of this type (Belfield & Crosta, 2012; Hodara & Cox, 2016; Ngo & Kwon, 2014; Scott-Clayton, 2012). However, studies have not included the effects of these changes on multilingual learners (MLLs).Using a census of every MLL placed in SXCC in the summer and fall of 2020 and the spring of 2021 (N = 12,603), a MANOVA found that MLL students in the SXCC system who were placed using previous placement methods had a higher overall GPA than students placed using self-reported GPA (M = 3.32, SD = 0.740; M = 2.01, SD = 1.27, respectively) and had higher satisfactory academic progress (SAP) (M = 102.98, SD = 51.52; M = 57.66, SD = 55.53, respectively), and took longer to enroll in English 101 (M = 5.11, SD = 3.55; M = 2.36, SD = 1.76, respectively).
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/tesj.835
Keywords: dept.edu; peer-reviewed